2023
DOI: 10.1001/jamanetworkopen.2023.5321
|View full text |Cite
|
Sign up to set email alerts
|

Definition and Criteria for Diagnosing Cesarean Scar Disorder

Abstract: ImportanceApproximately 60% of women develop a uterine niche after a cesarean delivery (CD). A niche is associated with various gynecological symptoms including abnormal uterine bleeding, pain, and infertility, but there is little consensus in the literature on the distinction between the sonographic finding of a niche and the constellation of associated symptoms.ObjectiveTo achieve consensus on defining the clinical condition that constitutes a symptomatic uterine niche and agree upon diagnostic criteria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…A Delphi consensus of 31 experts from three continents proposed the term ‘Cesarean Scar Disorder (CSDi)’ to capture these symptomatic CSDs. This disorder is characterized by at least one primary, or two secondary symptoms in a patient with sonographic evidence of a uterine niche (Table 1) [10 ▪ ].…”
Section: Clinical Signs and Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Delphi consensus of 31 experts from three continents proposed the term ‘Cesarean Scar Disorder (CSDi)’ to capture these symptomatic CSDs. This disorder is characterized by at least one primary, or two secondary symptoms in a patient with sonographic evidence of a uterine niche (Table 1) [10 ▪ ].…”
Section: Clinical Signs and Symptomsmentioning
confidence: 99%
“…Although obstetrical sequalae such as cesarean scar ectopic pregnancies, uterine dehiscence, and placenta accreta spectrum can be associated with the presence of a CSD, the experts concluded that these issues should be reported as complications of the CSDi, as opposed to symptoms. Furthermore, there was insufficient evidence to determine whether spontaneous abortion should be considered as a symptom related to the CSDi, or an independent problem [10 ▪ ].…”
Section: Clinical Signs and Symptomsmentioning
confidence: 99%
“…Morris advocated calling these symptoms cesarean scar syndrome 50 . Since the term describing this condition was not unified, a task force was established to avoid confusion under these conditions 51 . This task force, which comprised experts with experience in the field, provided results using the electronic Delphi method.…”
Section: Symptoms Associated With Csd and Its Nomenclaturementioning
confidence: 99%
“…However, some points must be considered during the diagnosis. First, the cause of AUB should be ruled out according to the International Federation of Gynecology and Obstetrics classification system (PALM‐COEIN) 51 . Symptoms must be confirmed in at least three menstrual cycles before diagnosis.…”
Section: Symptoms Associated With Csd and Its Nomenclaturementioning
confidence: 99%
“…Furthermore, diverticula may cause inaccessibility to the uterine cavity, causing problems during intrauterine insemination or embryo transfer. 8 Various explanations for the cause of subfertility after cesarean section have been proposed in the literature, including uterine pathology such as adenomyosis, pelvic adhesions, and women's reproductive choices, 9 but there are few reports on the effects of diverticula on fertility or assisted reproductive outcomes.…”
Section: Introductionmentioning
confidence: 99%